AN OVERVIEW OF ESCHERICHIAE COLI CONTAMINATION IN REFILL DRINKING WATER DEPOT IN PASAR MINGGU DISTRICT - Rudy Pou; Risna M. Riskawa; Rachel Marliana; Bedwina Rachmayanti; Farra Assyifa Rizqy; Nabilah Putri Amiyanti (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2023)
Background: Community needs to be protected from risk waterborne disease due to drinking water drinking from drinking water depots does not meet quality standards and sanitary hygiene requirements. Drinking water depots can be at risk of becoming a medium of transmission of various diseases if they do not meet health requirements. One indicator of the biological parameter of drinking water needs is the presence of Escherichia coli which must be found 0 (zero) per 100 ml of water in refill drinking water depots. The purpose of this study was to describe the quality of refill drinking water and the difference in factors between the depot that detected E.coli in its products and the depot that did not detect E.coli. Methods: This research was conducted at a refill drinking water depot in Pasar Minggu, Jakarta with a qualitative method through observation, in-depth interviews, and document studies. The study was conducted in July 2022. Results: The results showed that 35% of depots in Pasar Minggu were contaminated with E.coli and depots with E.coli 0 (zero) were more adaptable to requirements related to raw water sources, gallon management, filtration and disinfection. DAMIU owners and workers have never attended DAMIU hygiene and sanitation training and received certification. All DAMIUs do not have a hygiene certificate from the DKI Jakarta Provincial Health Office.